Pengaruh Persepsi Risiko terhadap Kepuasan Konsumen Melalui Kepercayaan Dalam E-marketplace - Ayu Rosita (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to find out: (1) Effect of risk perceptions on trust on Tokopedia site (2) Effect of trust on customer satisfaction on Tokopedia site (3) Effect of risk perceptions on customer satisfaction on Tokopedia site (4) Effect of risk perception and trust in satisfaction consumers on the Tokopedia site. The research method used in this study was a survey. The population in this study were UST Yogyakarta students who had shopped using Tokopedia. The sampling technique used purposive sampling method with a total sample of 100 people. Data collection techniques using questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression. The results of the data analysis with a significance of 0.05 indicate that there is a positive influence on risk perception on trust on the Tokopedia site. There is a positive influence of trust on customer satisfaction on the tokopedia site. There is a positive influence on the risk perception of consumer satisfaction on the Tokopedia site. There is a positive influence on the perception of risk and trust in customer satisfaction on the tokopedia site.